Environmentally sound management of ship wastes: Challenges and opportunities for European ports - Gabriela Argüello (Journal of Shipping and Trade (JST), 2020)
Ship wastes are incidentally regulated within the regime of marine pollution and the prevention of ship-source pollution is heavily reliant on the provision of adequate port reception facilities on land. However, the coordination between these facilities and further downstream management operations is still an unresolved issue. This paper examines from a legal perspective the challenges and opportunities related to the management of wastes generated on-board vessels after they are discharged to port reception facilities. Ship wastes are studied from a European Union (EU) law perspective and the author evaluates the integration of ship waste management within wider EU waste legislation and national waste management plans.
Keywords: 650; Ship wastes; Port reception facilities; Sea/land interface; Waste management; Directive (EU) 2019/883